The quality of mosque facilities provision for elderly and disabled (OKU) people at Seri Iskandar, Perak / Hadif Azwar Hasnizam - Hasnizam, Hadif Azwar (Universiti Teknologi Mara, Perak, 2021)
Disabled accessibility of a building is something that is very important to set up, especially in the mosque became the center of Muslim activity. The disabled are those who are less fortunate and are among those who have limited mobility caused them difficult to access to existing facilities at the mosque. However, most mosques in Malaysia do not fulfil these requirements in terms of providing facilities for the disabled people. This adversely affects them to engage in the social and economic mainstream. This study aims to identify the quality of mosque facilities provision for elderly and disable people.. This study using observation and questionnaire survey for the target respondent who stayed at Seri Iskandar. This data collection method are used to collect the data and comment on The Quality Of Mosque Facilities Provision For Elderly And Disabled (OKU) People At Seri Iskandar, Perak. The mosque involved in this study were Masjid Sultan Yussuf Izzudin Shah, Seri Iskandar, Perak Darul Ridzuan. The findings shows that the mosques is still not being "disabled friendly" where there are no facilities and special facilities accessible to people with disabilities. The recommendation of the design as proposed items at the external and internal will make the space more organized, having aesthetic value and practical for thus elderly and disabled people especially and all Muslim Ummah generally. This is will be blown up the integrity of Muslim ‘Ummah’, elderly and disabled people especially to achieve the real ‘ummah’ as a real Muslim